PEMBUATAN PROFIL INSTANSI BALAI PEMBUATAN PROFIL INSTANSI BALAI PENYULUHAN PERTANIAN KECAMATAN BELIK BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER - Shidqi Muhamad Zen (JURNAL ILMIAH INFORMATIKA, 2022)
Belik Subdistrict Agricultural Extension Center (BPP Belik) is a government extension agency that fosters farmers in Belik village. Every month at BPP Belik many activities are carried out. Both indoor activities and outdoor activities. The PPL (Field Agricultural Extension) officers provide a lot of training and coaching to farmers in Belik Village. However, the involvement of the participating farmers is still very limited, considering that BPP Belik has very limited funds and time. This makes information not spread evenly to farmers in Belik Village. Dissemination of information in the form of training or articles evenly will certainly increase agricultural production. Based on the existing problems, it is necessary to have a new information system, namely the creation of a website profile of the Belik District Agricultural Extension Center as an effort to provide alternative solutions for PPLs in disseminating information to farmers. The development of information systems on the website profile of the Belik District Agricultural Extension Center is using the waterfall method. Which consists of the analysis process, system design, design and implementation. The data analysis stage was obtained from interviews. Creating a website profile for BPP Belik agencies using the PHP programming language and MySql database. As well as using the php Codeigniter framework. The system trial on the BPP Belik Agency profile website is using the black box method. This test was carried out by 2 admins and writers at BPP Belik. The tests carried out are testing the appearance / user interface on the admin page and on the main page of the website.